GLP-1 receptor agonists synergistic effects of metabolic reprogramming and cardioprotection - Wang, Xuan; Qi, Mengmeng; Yang, Lili; Yang, Libo; Wang, Xiaoyue; Zhang, Fang; Cui, Yukun; Wang, Dongxin; Wang, Yangang; Lv, Wenshan (Frontiers in Endocrinology, 2025)
Diabetes mellitus, a condition that significantly elevates the incidence and mortality risks associated with cardiovascular diseases, exacerbates the disease burden in China. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have garnered considerable attention, as they not only regulate blood glucose but also play a vital role in safeguarding the cardiovascular system. Recent research shows that metabolic reprogramming is a key mechanism for the cardioprotective effects of GLP-1RAs. GLP-1RAs can achieve metabolic reprogramming by regulating fatty acid, glucose, and ketone body metabolism, as well as mitochondrial function. This process optimizes cardiac energy metabolism, alleviates oxidative stress, and reduces the risk of cardiovascular diseases. This review provides a comprehensive summary of the energy metabolism under normal cardiac conditions and the metabolic reprogramming involved in diabetes-related heart disease. The potential applications and challenges of targeted metabolic reprogramming in the cardioprotective effects of GLP-1RAs are further discussed.